النظام القانوني للمؤسسات الصغيرة والمتوسطة ودورها في تحقيق التنمية الاقتصادية - بكاري مسعودة بكاري, مسعودة; قعيد, وناسة (Universté ELOUEd-جامعة الوادي, 2023)
ىذه الد ا رسة تتحدث حول المؤسسات ص و م في الج ا زئر والدور الكبير الذي تمعبو في الاقتصاد وأيضا الآليات الميمة في ترقية المالية ولذلك أنشأت السمطات الج ا زئرية مجموعة من الآليات واليياكل لدعم ىذه المؤسسات والارتقاء بيا وىذا ييدف إلى تقديم الدعم المالي. لذلك ىذا البحث واضح لدور المؤسسات الصغيرة والمتوسطة في مجال التشغيل لذلك الحكومة الج ا زئرية تحاول طرح العديد من الطرق والسياسيات من أجل توفير فرض العمل والتشغيل من البطالة في إطار عمل ب ا رمج التنمية و الإنعاش الاقتصادي من خلال اتخاذ مجموعة من الإج ا رءات والقوانين التي تستيدف زيادة عدد ىذه الشركات وتحسينيا تيدف ىذه الد ا رسة إلى إعطاء نظرة واسعة حول الاست ا رتيجيات الاقتصادي المتطورة في الج ا زئر وعلاقتيا بالمؤسسات ص و م و تأثيرىا عمى مختمف المجالات الاقتصادية كالتوظيف وتنمية الصاد ا رت وخمق القيمة المضافة أيضا المؤسسات ص و م تعاني من عدة ع ا رقيل وتحديات تقمل من سريانيا بشكل صحيح. وىذا مما أدى إلى اقت ا رح جممة من الحمول.Therefore, the Algerian authorities have established a set of mechanisms and structures to support and upgrade these institutions and this aims to provide financial support. Also, the goal of this research is clear to the role of small and mediumsized enterprises in the field of employment, so the Algerian government is trying to put forward many ways and policies in order to provide employment and employment from unemployment within the framework of development programs and economic recovery by taking a set of measures and laws aimed at increasing the number of Also, the aim of this study is to give a broad view on the evolving economic strategies in Algeria and their relationship with the P & M institutions and their impact on various economic fields such as employment, Export Development and value added creation Also, the Y and M institutions suffer from several obstacles and challenges that reduce their proper functioning. This led to the proposal of a number of solutions.
مذكرة ماستر
Keywords: المؤسسات الصغيرة والمتوسطة الاقتصاد آليات تحسن المالية البطالة - - - – – مناصب العمل التشغيل الشركات تطور الاستثمار.; Small and medium enterprises – economy – mechanisms - financial improvement - unemployment - employment positions - employment - Enterprises-Investment Development.